Periodic Microstrip Leaky Wave Antenna with Double-Sided Shorting Pins and Pairs of Slots - Yahuan Chen; Kuang Wang; Yuanxin Li; Yunliang Long (International Journal of Antennas and Propagation)
A backward to forward scanning periodic microstrip leaky wave antenna (MLWA) is presented. The proposed antenna consists of a long rectangular patch with alternating shorting pin on each side, which connects the antenna patch and the ground plane to form periodic shorting circuits. There are two pairs of slots alternately spaced on the long patch to suppress the open stop band (OSB). The OSB problem was initially reduced by optimizing the structural parameters, and the slotting on the patch further improved it. The measured radiation pattern in the y-z plane shows that the antenna can scan electronically from 142° to 39° toward the end-fire (+z direction) when the operating frequency changes from 6 GHz to 12.9 GHz. The measured gain is greater than 5 dBi over the entire operating band.